2010
DOI: 10.1152/ajprenal.00169.2010
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor 23 production in bone is directly regulated by 1α,25-dihydroxyvitamin D, but not PTH

Abstract: Fibroblast growth factor 23 (FGF23), which is primarily produced by osteocytes in bone, regulates renal phosphate excretion and 1α,25-dihydroxyvitamin D [1,25(OH)(2)D(3)] metabolism. Patients with chronic kidney disease (CKD) have increased levels of circulating serum FGF23, but the direct effect on circulating FGF23 levels in renal insufficiency is still unclear. To identify the major regulator of FGF23 synthesis in renal insufficiency, we compared the effect of parathyroid hormone (PTH) and 1,25(OH)(2)D(3) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(51 citation statements)
references
References 40 publications
1
47
0
3
Order By: Relevance
“…Some researchers reported that calcitriol stimulates FGF23 synthesis in the calvarium of rats (29) and increases circulating FGF23 levels in thyroparathyroidectomized rats (30). These reports collectively indicate that PTH may indirectly stimulate FGF23 secretion by stimulation of calcitriol synthesis.…”
Section: Resultsmentioning
confidence: 94%
“…Some researchers reported that calcitriol stimulates FGF23 synthesis in the calvarium of rats (29) and increases circulating FGF23 levels in thyroparathyroidectomized rats (30). These reports collectively indicate that PTH may indirectly stimulate FGF23 secretion by stimulation of calcitriol synthesis.…”
Section: Resultsmentioning
confidence: 94%
“…7) Regarding the regulatory mechanisms of Fgf23 gene expression, it has been shown that Fgf23 expression is directly induced in osteocytes by ligand-bound vitamin D receptor. 19) Recently, Meir et al reported that an orphan nuclear receptor, Nurr1 also mediates increased Fgf23 expression by parathyroid hormone. 20) In this report, we revealed that NF-κB, a common mediator of TLR signaling, is essential for Fgf23 induction at least in cultured DCs.…”
Section: Discussionmentioning
confidence: 99%
“…effect on fgf23 expression in bone cells (13,14), raising uncertainty as to whether PTH directly affects FGF23 synthesis at all. Further studies are needed to reconcile these results and to clarify the direct effects (1-34) PTH on FGF23 expression.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, continuous subcutaneous infusion of (1-34) PTH increased circulating FGF23 levels in mice and in parathyroidectomized rats (10,12). Notably, however, other studies showed opposite effects (13)(14)(15).…”
Section: Introductionmentioning
confidence: 96%